2011
DOI: 10.1136/gutjnl-2011-301086
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer risk and levels of trace elements

Abstract: Background and aims Knowledge on the etiology of exocrine pancreatic cancer (EPC) is scant. The best established risk factor for EPC is tobacco smoking. Among other carcinogens, tobacco contains cadmium, a metal previously associated with an increased risk of EPC. We evaluated the association between concentrations of trace elements in toenails and EPC risk. Methods The study included 118 EPC cases and 399 hospital controls from Eastern Spain. Levels of twelve trace elements were determined in toenail sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
124
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(139 citation statements)
references
References 65 publications
(46 reference statements)
10
124
3
2
Order By: Relevance
“…Upon analysis, samples were weighed and digested in Optima nitric acid (Fisher Scientific, St. Louis, MO, USA) by low-pressure microwave digestion at the Trace Element Analysis (TEA) Core Laboratory (Dartmouth College, Hanover, NH, USA). 30 After digestion, the final sample weight was recorded and samples were then analyzed for total arsenic, measured in μ g total arsenic per g toenail ( μ g/g), using inductively coupled plasma mass spectrometry (ICPMS) on an Agilent 7700× (Agilent Technologies Headquarters, Santa Clara, CA, USA). Arsenic was detected in all but one infant toenail sample.…”
Section: Methodsmentioning
confidence: 99%
“…Upon analysis, samples were weighed and digested in Optima nitric acid (Fisher Scientific, St. Louis, MO, USA) by low-pressure microwave digestion at the Trace Element Analysis (TEA) Core Laboratory (Dartmouth College, Hanover, NH, USA). 30 After digestion, the final sample weight was recorded and samples were then analyzed for total arsenic, measured in μ g total arsenic per g toenail ( μ g/g), using inductively coupled plasma mass spectrometry (ICPMS) on an Agilent 7700× (Agilent Technologies Headquarters, Santa Clara, CA, USA). Arsenic was detected in all but one infant toenail sample.…”
Section: Methodsmentioning
confidence: 99%
“…As such, the negative effect of Cd on pulmonary tumour formation was indicated in both epidemiological and experimental studies [14,90,91]. There is also clear evidence of cancer progression due to Cd toxicity within the prostate [9294], kidney [95,96], breast [97,98], endometrium [99], bladder [100103] and pancreas [14,104–106]. Evidence for the involvement of Cd in the development of stomach, liver and hematopoietic cancers, however, is not very convincing [14,107].…”
Section: Cancermentioning
confidence: 99%
“…[40] Elevated levels of As in toenails are positively correlated with exocrine pancreatic cancer. [41] This correlation is stronger for higher levels of arsenic in drinking water. For low to moderate levels of exposure to inorganic As in water, the correlation increases for prolonged exposures.…”
Section: Introductionmentioning
confidence: 96%
“…It is interesting to note that in these studies it was found that high concentrations of selenium in toenails were anti-correlated with the risk of pancreatic cancer. [41] Toenail As levels were also studied in association with decreased DNA repair in individuals exposed to arsenic in drinking water. [42] In a recent study conducted in Bangladesh, it was shown that a logarithmic decrease in toenail arsenic content from baseline to follow-up measurements was related to decreased levels of arsenic in drinking water, and was significantly correlated with reduced skin lesion severity.…”
Section: Introductionmentioning
confidence: 99%